2005
DOI: 10.1021/ic0504543
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Azido−Copper(II) Bridges:  Ferro- or Antiferromagnetic? Experimental and Theoretical Magneto−Structural Studies

Abstract: Reaction of NaN(3) with the [Cu(II)(tn)](2+) ion (tn = 1,3-diaminopropane) in basic aqueous solution yields the azido-bridged complex of formula [Cu(2)(tn)(2)(N(3))(4)] (1), which is characterized by X-ray crystallography. The structure of 1 is made up of dinuclear neutral complexes, of formula [Cu(2)(tn)(2)(N(3))(4)], resulting from the assembling of two mononuclear units through two equivalent end-on azide bridges connecting asymmetrically two Cu(tn)(N(3))(2) entities. These dinuclear units are connected thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
88
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 165 publications
(99 citation statements)
references
References 50 publications
(104 reference statements)
11
88
0
Order By: Relevance
“…It explains the weak antiferromagnetic exchange observed in 1. Similar conclusion has also been drawn by other groups [31].…”
Section: Magnetic Properties and Epr Spectroscopysupporting
confidence: 92%
See 1 more Smart Citation
“…It explains the weak antiferromagnetic exchange observed in 1. Similar conclusion has also been drawn by other groups [31].…”
Section: Magnetic Properties and Epr Spectroscopysupporting
confidence: 92%
“…On the other hand, due to the absence of any meaningful overlap between magnetic orbitals, basalapical bridges usually give rise to very small magnetic couplings for end on modes [24][25][26][27][28][29][30][31]. Same is the case for the end to end dca bridged complexes due to relatively longer distance between the copper(II) centres [32][33].…”
Section: Introductionmentioning
confidence: 99%
“…[60,61] Broken Symmetry (BS) DFT calculations have turned out to reach agreement with experiments for dinuclear copper(II) systems as well as for several families of compounds. [13,27,34] J is directly accessible using Noodlemanns expression [Eq. (5)]:…”
Section: Neutron Diffraction Structure Determinationmentioning
confidence: 99%
“…[20,25] In the last five years, this picture has changed somewhat because more azido-bridged copper(II) dinuclear complexes have been reported. Some asymmetric EO systems [11][12][13] have now been found that exhibit antiferromagnetic Cu À Cu interactions, while several cases of ferromagnetic couplings have been reported for asymmetric EE systems. [11,22,23] In the early studies, [3][4][5][6][17][18][19][20] the symmetric EO coordination mode behavior seemed intrinsically ferromagnetic and independent of any structural parameters.…”
mentioning
confidence: 99%
“…Very recently, magnetostructural correlations for such asymmetrically bridged compounds based on DFT calculations have been proposed. [14] Nevertheless, synthesis and physical characterization of new azido-bridged coordination complexes are still of interest to define the structural factors governing the exchange coupling between azido-bridged paramagnetic centers, since magnetostructural correlations have only been proposed for a few systems such as basal-basal end-on Cu II[15] and Mn II[16] compounds. Interestingly, we have shown that the synthesis of POM/N 3 À complexes leads to azido compounds characterized by original structural features that differ from those obtained using organic ligands.…”
Section: Introductionmentioning
confidence: 99%